PENGARUH RADIASI SINAR GAMMA TERHADAP PERTUMBUHAN DAN PERUBAHAN FENOTIPE TUNAS IN VITRO LIDAH BUAYA (ALOE VERA) - Imelda, M; Sari, S; Wulansari, A; Eriyandri, F (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2011)
Aloe vera (L.) Burm.f. of the Asphodelaceae, which probably originated in North AfricaÃ‚Â is a very short-stemmed succulent, perennial plant of 80-100 cm in height. Today, itÃ‚Â is widely grown in the tropics worldwide. It has long been used as a traditional herbalÃ‚Â medicine and as cosmetic materials since thousand of years BC in Egypt, China,Ã‚Â Greece, etc. It can be used externally to treat various skin conditions and It was usefulÃ‚Â for curing diabetics, cancer, HIV, even for stress and drug addicts The biologically activeÃ‚Â components found in the juice of aloe leaves are anthraquinones, acemannan, andprostaglandins. Chunks of aloe pulp are popular as beverages in Asia. Aloe has longÃ‚Â been propagated by splitting its off-shoots, and this may account for its narrow geneticÃ‚Â variations. In this research, genetic variations of A. vera and A. vera var. Chinensis, wereÃ‚Â induced by gamma irradiation. In vitro shoots of Aloe were irradiated with gamma ray atÃ‚Â the dosage of 10-60 gy, then propagated on Murashige and Skoog (MS) solid mediumÃ‚Â containing 1 mg/l BAP. The results showed that shootlets of A. vera var. ChinensisÃ‚Â were still alive up to 40 gy but the leaves became stiffer, while A. vera only toleratedÃ‚Â irradiation up to 20gy. At 50-60 gy, all cultures died after 2 months. Visual observationÃ‚Â on irradiated in vitro shoots showed that new variants appeared at the dosage of 20 gy,Ã‚Â although in very low frequencies. Leaves became half green and half white in A. veraÃ‚Â and white-green-white in A. vera var. Chinensis. Confirmation whether those variantsÃ‚Â were of genetic or morphological origin needs to be further investigated.